PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS: META ANALISIS - Fia Ayuning Pertiwi; Reza Hilmy Luayyin; Mohammad Arifin (LPPM STAI Muhammadiyah Probolinggo, 2023)
The misunderstandings of the Indonesia people often lead to conflicts and controversies. Critical thinking skill is defined as the process of analyzing evidence in analyzing all forms of information to find a decision so as not to be carried away by negative currents. One of the special solutions needed to improve critical thinking skills can be done through educational programs, namely by applying appropriate learning methods and models. The PBL models offers learning that is able to solve problems in applying freedom to students in developing communication skills and problem solving skills to face the world of education. The purpose of this research is to analyze the PBL learning model can improve critical thinking skills. The method used in this meta-analysis. The research begins by collecting relevant data through Google Scholar for analysis. Research from the 30 data obtained, 10 relevant articles were obtained. Based on the results of the search data, the PBL learning model was able to improve students’ critical thinking skills. Keywords: The Problem Based Learning, Critical Thinking Skills, Learning.